2013
DOI: 10.3389/fpsyg.2013.00601
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetry in infants' selective attention to facial features during visual processing of infant-directed speech

Abstract: Two experiments used eye tracking to examine how infant and adult observers distribute their eye gaze on videos of a mother producing infant- and adult-directed speech. Both groups showed greater attention to the eyes than to the nose and mouth, as well as an asymmetrical focus on the talker's right eye for infant-directed speech stimuli. Observers continued to look more at the talker's apparent right eye when the video stimuli were mirror flipped, suggesting that the asymmetry reflects a perceptual processing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 67 publications
(97 reference statements)
0
11
0
Order By: Relevance
“…Some studies have shown that adults from Western cultures tend to look at the eyes more than the mouth during audiovisual speech perception in no noise (Smith, Giblisco, Meisinger, & Hankey, ; Vatikiotis‐Bateson, Eigsti, Yano, & Munhall, ), while others have observed a preference for the mouth over the eyes (Barenholtz, Mavica, & Lewkowicz, ). What appears to differentiate these two different findings is that the allocation of visual attention to the face during speech perception is highly dependent on task demands.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have shown that adults from Western cultures tend to look at the eyes more than the mouth during audiovisual speech perception in no noise (Smith, Giblisco, Meisinger, & Hankey, ; Vatikiotis‐Bateson, Eigsti, Yano, & Munhall, ), while others have observed a preference for the mouth over the eyes (Barenholtz, Mavica, & Lewkowicz, ). What appears to differentiate these two different findings is that the allocation of visual attention to the face during speech perception is highly dependent on task demands.…”
Section: Introductionmentioning
confidence: 99%
“…Along with changes in visual influence on speech perception, there are also developmental changes in gaze patterns to the face. Infants younger than 8 months old show a preference for watching the eyes both during infantdirected and adult speech (Lewkowicz & Hansen-Tift, 2012;Smith et al, 2013). At around 8 months old, infants shift their attention to the mouth of a speaking face but return to focus on the eyes again by 12 months old (Lewkowicz & Hansen-Tift, 2012;Pons, Bosch, & Lewkowicz, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The increased time spent looking at faces may reflect infants' growing understanding that faces are a significant source of social information (Frank et al, 2009 , 2012 ), but it may also reflect the fact that they are becoming increasingly proficient at processing dynamic cues (e.g., Wattam-Bell, 1996 ; Braddick et al, 2003 ), and increasingly sensitive to intersensory redundancy (e.g., the match between speech sounds and moving mouths) (Bahrick and Lickliter, 2000 ). The fact that infants' attention to faces becomes especially marked when they are listening to a speaker (Smith et al, 2013 ; Tenenbaum et al, 2013 ) supports the view that they use visual cues (lip movements) to facilitate speech perception (e.g., Bristow et al, 2009 ), although their ability to integrate visual and auditory speech cues is not as strong as that of adults (Desjardins and Werker, 2004 ).…”
Section: Introductionmentioning
confidence: 96%
“…This enhancement may rely on correlations between head movement and stress patterns in speech (Hadar et al, 1983; Hadar, Steiner, Grant, et al, 1984). Although, infants are sensitive to audiovisual correspondences in speech (Kuhl & Meltzoff, 1982; Patterson & Werker, 2002, 2003) and have shown enhancement in learning with visual speech (Teinonen et al, 2008), it remains unclear the degree to which this enhancement relies on oral versus extraoral visual information (Lewkowicz & Hansen-Tift, 2012; Smith, Gibilisco, Meisinger, & Hankey, 2013). The finding that infants are able to match the emotional expression of talking faces with emotional speech, even when the area around the mouth is obscured (Walker-Andrews, 1986), suggests that infants use extraoral visual information in speech perception.…”
Section: Discussionmentioning
confidence: 99%